Estimation of motivation using entropy - Srivastava, Sachin Kumar; Kakkar, Dhruve Narain (Journal of Business Economics and Management, 2008)
Motivation has been in practices since the life of mankind. It is such an effort, which requires to be quantified for better management technique. The present paper deals with estimation of motivation efforts using entropy and ability of manpower involved in certain organization.First published online: 14 Oct 2010